Comparison of the Regenerative Metabolic Efficiency of Lipid Extracts from Microalgae Nannochloropsis oceanica and Chlorococcum amblystomatis on Fibroblasts - Anna Stasiewicz; Tiago Conde; Maria do Rosario Domingues; Pedro Domingues; Michał Biernacki; Elżbieta Skrzydlewska (MDPI AG, 2024)
UVA radiation leads to oxidative stress and inflammation in skin cells. Therefore, the aim of this study was to compare the effect of lipid extracts from microalgae Nannochloropsis oceanica (N.o.) (marine) and Chlorococcum amblystomatis (C.a.) (freshwater) on the redox balance and PUFA metabolism in human skin fibroblasts modified by UVA. Lipid extracts from both types of microalgae introduced into the fibroblast medium after UVA irradiation significantly reduced the level of ROS and enhanced expression of Nrf2, which increased the activity/level of antioxidants (SOD1/2, CAT, GSH, Trx). The reduction in oxidative stress was accompanied by a decrease in the level of 4-HNE, its protein adducts and protein carbonyl groups. Microalgae also reduced the activity of COX1/2, FAAH and MAGL increased by UVA, and as a consequence, the level of lipid mediators (especially after N.o.) decreased, both from the group of endocannabinoids (AEA, 2-AG, PEA) and eicosanoids (PGE2, 15d-PGJ2, TXB2, 15-HETE), acting mainly through receptors related to G protein, the expression of which increases after UVA. This further contributed to the reduction in oxidative stress and pro-inflammatory signaling at NF-κB and TNFα levels. Therefore, it is suggested that lipid extracts from both N.o. and C.a. microalgae can be used to regenerate fibroblast metabolism disturbed by UVA radiation.